Effect of Chromium added Basal Diet on Serum Glucose, Insulin, Cortisol, Alkaline Phosphatase and Feedlot Performance in Rabbits - Şahin, Kazım; Haul Çerçi, I.; Güler, Talat; Şahin, Nurhan; Erkal, Necla (Scientific and Technical Research Council of Turkey, 1997)
This experiment was conducted to evaluate the effect of chromium added basal diet [Basal diet (539.17 chromium) = Control Group. Basal Diet + 200 ppb Chromium = 200 ppb Group. Basal Diet + 400 ppb Chromium = 400 ppb Group] on some biochemical parameters of pregnant rabbit and their offspring. The similar effect was investigated on feed intake, daily gain, feed efficiency and some biochemical parameters in the rabbits fed up after weaning. Average daily gain, average daily feed intake and gain/feed were not affected by addition of chromium (P>0.05). By addition chromium to basal diet, serum glucose was decreased in all periods of rabbits (Pregnant, offspring, rabbit fed up), but this decreasing was not significant statistically. Serum alkaline phosphatase activity and insulin concentration were increased by dietary treatment in all periods, and cortisol concentrations was decreased but. this differences were not significant statistically.
Tavşanlarda Bazal Rasyona Krom İlavesinin Glikoz, İnsulin, Kortizol ve Alkali Fosfataz Düzeyleri ile Besi Performansi Üzerine Etkisi
Keywords: Alkaline phosphatase; Chromium; Cortisol; Feedlot performance; Glucose; Insulin; Rabbit